PENGARUH KOMPLEKSITAS TUGAS, TEKANAN KETAATAN, PENGALAMAN AUDITOR TERHADAP AUDIT JUDGMENT (Studi Empiris Pada Auditor Kantor Akuntan Publik Kota Medan) - Apliniari Yuniar; Reza Hanafi Lubis (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2022)
A professional auditor is seen in fulfilling his duties and responsibilities. The purpose of this study was to determine the effect of task complexity, compliance pressure, and auditor experience on audit judgment (an empirical study of auditors at KAP in Medan). This research is a type of quantitative research. The data collection method used in this study was a questionnaire. There are 23 KAP residents and a total of 185 permanent auditors. The research sample was determined based on saturated sampling and only 6 KAPs were accepted, so the sample used was 40 auditors. The data analysis technique of this study used multiple linear regression analysis using SPSS Version 25. The results of this study indicate that: 1. Task complexity has no effect 2. Appropriate pressure has an effect on rating review. 3. The experience of the auditor has a significant influence on the work of the auditor.4. Task complexity, compliance pressure and auditor experience simultaneously have a significant impact on the assessment score.